Optimization of executive functions from habit education in kindergarten through the principles of Universal Design for Learning - Martínez Ocaña, María Jesús; Navarro Martínez, Oscar (Journal of Learning Styles, 2025)
The aim of this study was to determine whether an educational intervention for eating and toileting habits, designed from the principles of Universal Design for Learning, contributes to the improvement of executive functions in two to three year old students in a nursery school. An educational intervention was designed and applied for the moments of eating and toileting habits during six months, evaluating its impact on the development of executive domains. A quasi-experimental approach was used with an experimental group and a control group, using the Spanish adaptation of the Behavioral Assessment of Executive Function questionnaire, child version, BRIEF-P as pretest and posttest to determine the changes associated with the habit intervention. Quantitative results show that this intervention promotes improvement in these executive domains, presenting eating and grooming habits as mediating tasks for executive function training.